THE EFFECT OF PROBLEM-BASED LEARNING WITH EXPERIMENT ON STUDENTS’ RESPONSES AND LEARNING OUTCOME IN THE REFLECTION AND REFRACTION CONCEPT LEARNING - Ary Norsaputra; Johansyah Johansyah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: In some previous studies, an inappropriate teaching and learning was one of the factors that caused many students’ misconception in the concept of reflection and refraction. Moreover, the students’ response was known as a factor that lead students to have a misconception, and lead to have a low learning outcome. Aims: This study aimed to study the effect of using of Problem-Based Learning on the students’ responses and learning outcome in learning the concept of light (reflection and refraction). Methods: The posttest only control design was applied in this study. The MCQs test and questionnaires of response were implemented to 27 students of grade 8th after the learning activity by using Problem-Based Learning with experiment. The data gained by both MCQs test and questionnaire were statistically analyzed. Results: About 74.07 % students had passed the minimum completeness criteria (KKM). Most of the students’ responses agreed that learning via Problem-Based Learning with experiment was helpful to understand the learning concept and to gain a new idea to solve the problem. In addition, the percentage of influencing of students’ response to the students’ learning outcome was 11 %. Conclusion: Teaching and learning via Problem-Based Learning with experiment had helped the students to get high learning outcome and good response. The results were also revealed that the students’ response was one of affecting factors on the students’ learning outcome.